2022
DOI: 10.1021/acschemneuro.2c00359
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Administration of Common Anesthetics Does Not Dramatically Change the Endogenous Peptide Profile in the Rat Pituitary

Abstract: Cell−cell signaling peptides (e.g., peptide hormones, neuropeptides) are among the largest class of cellular transmitters and regulate a variety of physiological processes. To identify and quantify the relative abundances of cell−cell signaling peptides in different physiological states, liquid chromatography−mass spectrometry-based peptidomics workflows are commonly utilized on freshly dissected tissues. In such animal experiments, the administration of general anesthetics is an important step for many resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 74 publications
3
6
0
Order By: Relevance
“…This result suggests that neither sodium pentobarbital nor isoflurane have dramatic effects on the overall peptide profile in the hypothalamus and cerebral cortex, which parallels our previous results from the pituitary. 26 We also did not detect any major sex-specific differences in the peptide profile (Figure S5). Within each tissue, pairwise comparisons for each experimental group were then performed to identify any individual peptides that significantly differ on the basis of treatment effect (Figures 2 and 3, Tables 1 and 2, and Tables S1−S4).…”
mentioning
confidence: 64%
See 2 more Smart Citations
“…This result suggests that neither sodium pentobarbital nor isoflurane have dramatic effects on the overall peptide profile in the hypothalamus and cerebral cortex, which parallels our previous results from the pituitary. 26 We also did not detect any major sex-specific differences in the peptide profile (Figure S5). Within each tissue, pairwise comparisons for each experimental group were then performed to identify any individual peptides that significantly differ on the basis of treatment effect (Figures 2 and 3, Tables 1 and 2, and Tables S1−S4).…”
mentioning
confidence: 64%
“…We previously demonstrated that the short-term (<5 min) use of isoflurane or sodium pentobarbital had minimal impact on the peptide profile in rat pituitary, thereby suggesting that acute anesthetic administration did not confound peptide profile in this endocrine organ. 26 In the present study, we aimed to extend our method to investigate the effect of anesthetic administration on two regions of the brain: the hypothalamus and the cerebral cortex. Both of these brain regions are relatively rich in endogenous peptides 4,27 and have previously been shown to be influenced by anesthetic administration.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Endogenous peptides were extracted from tissues using both organic and aqueous extraction steps and enriched using molecular weight-based centrifugation filtration devices and solid-phase extraction. Extracted peptides were analyzed by a LC–MS and LC–MS/MS-based label-free peptidomics workflow, , which includes steps for data filtering, batch correction, imputation, and normalization (Figures S2–S5). Following data processing and normalization, relative peptide abundances were compared between groups using multivariate and univariate statistical analyses.…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesized that changes in cell–cell signaling peptides from the hypothalamus and pituitary may be responsible for regulating critical physiological changes during the hibernation season. To test this hypothesis, we applied a non-targeted liquid chromatography–mass spectrometry (LC–MS) and LC-tandem mass spectrometry (LC–MS/MS) “peptidomics” approach , to identify and quantify endogenous neuropeptides and peptide hormones as a function of season and hibernation stage in the thirteen-lined ground squirrel. LC–MS and LC–MS/MS-based peptidomics allow the detection, identification, and quantification of peptides without preselection, allowing for findings not possible with targeted antibody-based methods.…”
Section: Introductionmentioning
confidence: 99%